An Analysis of Causes of Students' Problems in Writing Recount Text - Nurkholijah Nurkholijah; Muhd Al Hafizh (Journal of English Language Teaching, 2020)
The objectives of this research were to know how were the causes of the students’ problems in writing recount text and the most dominant causes of problems in writing recount text. The online research was conducted on 21 Mei 2020 at google form. In this research, the Senior High Schools’ Students of West Sumatera that had studied recount text as the subject, with the total of respondents are 80 students. The researcher used questionaire as the instrument of this research and using descriptive qualitative method. To analyze the result of this research, the researcher used descriptive analysis. The finding of this research shows that there were four indicators of causes that made students had problems in writing recount text, they were interference first language, lack knowledge in grammatical rules, lack of vocabulary and difficult in organization. Then, the most dominant causes that made students had problems in writing recount is interference first language with the percentage is 86.3%, followed by lack of vocabulary with the percentage is 74.5%, lack knowledge in grammatical rules with the percentage is 68%, and the last is difficult in organization with 48.45%.